Issues in the Implementing of Online Learning in Islamic Higher Education During the Covid-19 Pandemic - Mahfud Junaedi; Nasikhin Nasikhin; Silviatul Hasanah (Ta'dib, 2022)
Our research aims to find out the problems experienced by students and lecturers in the implementation of online learning, during the Covid-19 pandemic and efforts to overcome styles in universities. Qualitative descriptive approaches and exploratory case studies were used to collect data from students and lecturers at the State Islamic University of Walisongo Indonesia. This study shows that the implementation of online learning during the COVID-19 pandemic has led to changes in the learning system that have led to a new lecture paradigm that can be highlighted in four sub-scales including the level of saturation, seriousness and participation in learning, learning motivation, and the level of intellectual satisfaction. Meanwhile, the efforts made by lecturers in overcoming this problem are by maximizing the use of learning technology tools, modifying certain learning methods such as project based learning, integrated curriculum, and blended learning. This study contributes to research on pedagogy and online learning by clarifying the role of lecturers in finding problem solving problems faced by students.